Recycling chains for lithium-ion batteries: A critical examination of current challenges, opportunities and process dependencies. (1st February 2022) - Windisch-Kern, Stefan; Gerold, Eva; Nigl, Thomas; Jandric, Aleksander; Altendorfer, Michael; Rutrecht, Bettina; Scherhaufer, Silvia; Raupenstrauch, Harald; Pomberger, Roland; Antrekowitsch, Helmut; Part, Florian
Graphical abstract: Highlights: LIB recycling chains and the interrelationships of the processes were reviewed. Consequences of individual process steps for the overall concept. Pyrolysis can have major impacts on the efficiency of downstream recovery processes. Both, the chemical and structural properties of black matter are decisive. Processing history of outputs/intermediates should be well documented and shared. Abstract: Lithium-ion batteries (LIBs) show high energy densities and are therefore used in a wide range of applications: from portable electronics to stationary energy storage systems and traction batteries used for e-mobility. Considering the projected increase in global demand for this energy storage technology, driven primarily by growth in e-vehicles, and looking at the criticality of some raw materials used in LIBs, the need for an efficient recycling strategy emerges. In this study, current state-of-the-art technologies for LIB recycling are reviewed and future opportunities and challenges, in particular to recover critical raw materials such as lithium or cobalt, are derived. Special attention is paid to the interrelationships between mechanical or thermal pre-treatment and hydro- or pyrometallurgical post-treatment processes. Thus, the unique approach of the article is to link processes beyond individual stages within the recycling chain. It was shown that influencing the physicochemical properties of intermediate products can lead to reduced recycling rates or even the exclusion of certain process options at the end of the recycling chain. More efforts are needed to improve information and data sharing on the exact composition of feedstock for recycling as well as on the processing history of intermediates to enable closed loop LIB recycling. The technical understanding of the interrelationships between different process combinations, such as pyrolytic or mechanical pre-treatment for LIB deactivation and metal separation, respectively, followed by hydrometallurgical treatment, is of crucial importance to increase recovery rates of cathodic metals such as cobalt, nickel, and lithium, but also of other battery components.